Prevalence and risk factors associated with Dirofilaria immitis infection in dogs in Makurdi, Benue State, Nigeria (Journal of Advanced Veterinary and Animal Research, 2017)
Objective: This study was designed to assess the prevalence and the associated risk factors (e.g., sex, age, breed, management system and climate) of Dirofilaria immitis in dogs in Makurdi metropolis in Nigeria.Materials and methods: Prevalence study of canine heartworm disease in dogs was conducted over a period of six months covering five localities of Makurdi metropolis in Benue State, Nigeria. A total of 186 blood samples were collected from apparently healthy and sick dogs, and the samples were examined for the presence of microfilaria between September 2015 and February 2016. Three methods (wet mount, Buffy coat and modified Knotts techniques) were used for the examination of the samples. The Packed Cell Volume (PCV) and complete blood count for each sample were also determined.Results:  Out of the 186 dogs, 4 (2.15%) were found to be positive for the presence of microfilaria. Out of the 4 positive cases, 3 (1.61%) were microfilaria and 1 (0.54%) was unidentified motile parasite. A total of 104 females were examined and only 1 (0.96%) was positive, while 3 (3.66%) males out of 82 examined were positive. Out of 141 older dogs examined, 4 (2.84%) were positive. Hematology of the positive dogs revealed mild anemia and moderate thrombocytopenia with Mean±SD of 34.8±15.30% and 108±60.81x109/L, respectively.Conclusion: The study confirms Knotts technique to be the most sensitive in the diagnosis of dirofilariasis in dogs using parasitological techniques. The findings confirm the occurrence of D. immitis in dogs in Makurdi with low prevalence and that the general public are at high risk of spreading infection from the dogs. Infection is more in male and adult dogs. This work can assist in planning appropriate strategies for controlling and prevention of D. immitis infection in Nigeria.http://doi.org/10.5455/javar.2016.c170